Hakikat Reward and Punishment Dalam Pendidkan Islam - Ahmad Suhaimi (JURNAL INDO-ISLAMIKA, 2014)
The study wants to provide an insight into the importance of reward and punishment in relation to education. It is realized that the learning method by using reward and punishment can encourage students to have motivation to learn. As for the results in this study Reward and punishment are techniques to touch someone's psychic side so that they understand if they make a mistake, as a result the child will continue to be optimistic if what he did is right and stop after making a mistake.